2018
DOI: 10.1038/s41598-018-27118-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the stimulation of S. pombe Dnmt2 catalytic efficiency by the tRNA nucleoside queuosine

Abstract: Dnmt2 methylates cytosine at position 38 of tRNAAsp in a variety of eukaryotic organisms. A correlation between the presence of the hypermodified nucleoside queuosine (Q) at position 34 of tRNAAsp and the Dnmt2 dependent C38 methylation was recently found in vivo for S. pombe and D. discoideum. We demonstrate a direct effect of the Q-modification on the methyltransferase catalytic efficiency in vitro, as Vmax/K0.5 of purified S. pombe Dnmt2 shows an increase for in vitro transcribed tRNAAsp containing Q34 to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 37 publications
(46 reference statements)
1
50
0
Order By: Relevance
“…Another function is illustrated by G37 N 1 ‐methylase (TrmD), which is critical for multi‐drug resistance (Masuda et al , 2019). In the yeast Schizosaccharomyces pombe , m 5 C38 is methylated by DNMT2(TRDMT1) methylase provided G34 has been replaced with queuine, a modified base that results from an atypical use of AdoMet [donation of its ribosyl – not its methyl – group (Johannsson et al , 2018; Muller et al , 2019)]. C38 methylation into m 5 C38 is widespread and plays an important role in stress‐related processes by protecting the anticodon from cleavage.…”
Section: Adomet‐dependent Methylations Of the Translation Machinerymentioning
confidence: 99%
“…Another function is illustrated by G37 N 1 ‐methylase (TrmD), which is critical for multi‐drug resistance (Masuda et al , 2019). In the yeast Schizosaccharomyces pombe , m 5 C38 is methylated by DNMT2(TRDMT1) methylase provided G34 has been replaced with queuine, a modified base that results from an atypical use of AdoMet [donation of its ribosyl – not its methyl – group (Johannsson et al , 2018; Muller et al , 2019)]. C38 methylation into m 5 C38 is widespread and plays an important role in stress‐related processes by protecting the anticodon from cleavage.…”
Section: Adomet‐dependent Methylations Of the Translation Machinerymentioning
confidence: 99%
“…c) ; the m 5 C38 modification introduced in mammals, Drosophila melanogaster , Arabidopsis thaliana , and S. pombe on tRNA Asp by the Dnmt2 family of enzymes, which is greatly stimulated by prior queuosine Q34 or mannosyl–queuosine manQ34 modifications (Fig. d) ; and the I34 modification introduced in Trypanosoma brucei on tRNA Thr(AGU) by ADAT2/ADAT3 heterodimer, which is stimulated by prior deamination of C32 leading to U32, which is itself stimulated by the prior methylation of C32 leading to m 3 C32 (Fig. e) .…”
Section: Prior Modifications In Trna Can Influence the Introduction Omentioning
confidence: 99%
“…70,71 Intriguingly, NSun2 promoted the expression of intercellular adhesion molecule-1 (ICAM-1) by methylating ICAM-1 mRNA, thereby increasing the adhesion of leucocytes to vascular endothelium. 74 Durdevic et al found that Dnmt2 interacted directly with viral RNA and played a role in anti-Drosophila C virus (DCV) immunity by possibly methylating viral RNA. Compared to wild-type rats, Hcy-stimulated NSun2(-/-) rats showed significantly reduced levels of ICAM-1 and leucocyte adhesion to endothelial cells.…”
Section: Trna Modifications and Immune Responsesmentioning
confidence: 99%
“…73 DNA methyltransferase-2 (Dnmt2) is another methyltransferase that methylates cytosine at position 38 of tRNA Asp and its catalytic efficiency is related to the tRNA nucleoside queuosine. 74 Durdevic et al found that Dnmt2 interacted directly with viral RNA and played a role in anti-Drosophila C virus (DCV) immunity by possibly methylating viral RNA. 75 New studies confirmed that defects in Drosophila Dnmt2 reduced immune function with age by affecting sphingolipid metabolism.…”
Section: Trna Modifications and Immune Responsesmentioning
confidence: 99%